MANAGERIAL SKILL CAMAT UNTUK MENINGKATKAN KINERJA PEGAWAI DI KECAMATAN CIAWI KABUPATEN BOGOR - Mote, Yohanes; Rahmawati, Rita; Seran, G. Goris (Jurnal Governansi, 2019)
This study aims to describe the managerial skill of district head to improve the civil servant performance in Ciawi District Bogor Regency. There are four managerial skills necessarily mastered by district head, namely conceptual skill, administrative skill, human relationship skill, and technical skill. The performance of civil servants consists of quality of work, pomptnees, initiative, capability, and communication. The method of this research is associative-quantitative in order to statistically test the relationship of variables by using Rank Spearman Correlation with SPSS version 18. The result of this research indicates coefficient correlation of the managerial skill of district head to the civil servant performance 0.699, categorized as strong. By t-test, it is gained t-counted 5.948 and t-table (N=27) 2.886; t-counted > t-table means that Ho is rejected and Ha is accepted. There is a strong relationship of managerial skill of district head to the civil servant performance. Coefficient determination indicates 48.8% that means contribution of the managerial skill of district head to the civil servant performance 48.8%. By counting Weight Mean Score, the managerial skill of district head gains the mean score 4.15 categorized as good. The civil servant performance gains the mean score 4.15 categorized as good. Keywords: Managerial Skill, District Head, Civil Servant Performance.